UNITED STATES INTERVENTION IN CUBA DURING THE COVID-19 PANDEMIC (ECONOMIC EMBARGO) - Suci Vajriyati (Journal of Social Political Sciences, 2022)
This research aims to find out why the United States still imposes an economic embargo on Cuba even though Cuba is experiencing an economic crisis and social turmoil that occurred amid the Covid-19 pandemic. By using a qualitative method, which places more emphasis on observing the phenomenon and more research into the substance of the meaning of the phenomenon. The data collected comes from literature, scientific journals, and official sources that are accessed via the internet. According to McCusker, K., & Gunaydin, S. (2015), this research is a qualitative descriptive analysis. This research combines Dependency (Dependence), Andre Gunder Frank, and International Economic Sanction Theory. The purpose of this writing is, that the author tries to research and explain based on facts the reasons for the United States still imposing an economic embargo on Cuba even though Cuba is experiencing an economic crisis and social turmoil that occurred amid the Covid-19 pandemic.